Dimetalla-heterocyclic carbenes: the interconversion of chalcocarbonyl and carbido ligands. Issue 83 (18th September 2020) - Barnett, Harrison J.; Hill, Anthony F.
Abstract : Different classes of dirhodium μ-carbido complexes cleave CS2 to afford mono- and bi-nuclear CS complexes, the CSe analogues of which are also described. Abstract : The μ-carbido complexes [Rh2 (μ-C)Cl2 (PPh3 )4 ] and [Rh2 (μ-C)Cl2 (dppm)2 ] cleave CS2 to afford the monothiocarbonyl complexes [RhCl(CS)(PPh3 )2 ] and [Rh2 (μ-CS)Cl2 (dppm)2 ]. The latter reacts with dimethyl acetylenedicarboxylate (DMAD) to afford [Rh(μ-CS)(μ-DMAD)Cl2 (dppm)2 ]. This complex is also formed from [Rh(μ-C)(μ-DMAD)Cl2 (dppm)2 ] and sulfur. These strategies also afford the first rhodium selenocarbonyl complexes [Rh(μ-CSe)Cl2 (dppm)2 ] and [Rh(μ-CSe)(μ-DMAD)Cl2 (dppm)2 ].